2006
DOI: 10.1159/000095135
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Modulation of the Intermediate- Conductance Ca<sup>2+</sup>-Activated K<sup>+</sup> Channel in Glioblastoma GL-15 Cells

Abstract: We report here the expression and properties of the intermediate-conductance Ca2+-activated K+ (IKCa) channel in the GL-15 human glioblastoma cell line. Macroscopic IKCa currents on GL-15 cells displayed a mean amplitude of 7.2±0.8 pA/pF at 0 mV, at day 1 after plating. The current was inhibited by clotrimazole (CTL, IC50=257 nM), TRAM-34 (IC50=55 nM), and charybdotoxin (CTX, IC50=10.3 nM). RT-PCR analysis demonstrated the expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
55
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 49 publications
(62 citation statements)
references
References 53 publications
7
55
0
Order By: Relevance
“…Previous studies have attributed the upregulation of KCNN4 channels to the activation of extracellular signal-regulated kinases (ERK1/2) in vascular smooth muscle cells (23,24) and that the NF-κB transcription factor critically regulates the expression of small conductance Ca 2+ channels (25). In agreement with these findings, we have shown that expression of TNF-α was increased with transfection of the PAcGFP-PRL-3 vector.…”
Section: Discussionsupporting
confidence: 89%
“…Previous studies have attributed the upregulation of KCNN4 channels to the activation of extracellular signal-regulated kinases (ERK1/2) in vascular smooth muscle cells (23,24) and that the NF-κB transcription factor critically regulates the expression of small conductance Ca 2+ channels (25). In agreement with these findings, we have shown that expression of TNF-α was increased with transfection of the PAcGFP-PRL-3 vector.…”
Section: Discussionsupporting
confidence: 89%
“…We found that mitogenic stimulation with bFGF induced a robust and rather selective up-regulation of the intermediate-conductance K Ca subtype K Ca 3.1 in renal fibroblasts. The principle signal transduction pathway involved in this mitogen-induced K Ca 3.1 up-regulation appeared to rely on the Ras/Raf/MEK/ERK-signaling cascade, which is in line with observations in other cell types (15,21,23,34). In contrast, expression levels of the related K Ca channels K Ca 1.1 and K Ca 2.3 were unchanged in response to bFGF, underscoring a certain specificity of K Ca 3.1 up-regulation and suggesting a pivotal role for K Ca 3.1 in the promotion of renal fibroblast proliferation.…”
Section: Discussionsupporting
confidence: 88%
“…Glioblastoma cells functionally express high numbers of Ca 2þ -activated IK K þ channels (other names are hIKCa1, hKCa4, hSK4, KCa3.1) in their plasma membrane (3)(4)(5)(6). Notably, IK channels are low expressed or even absent in human astrocytes (7) but upregulated during neoplastic transformation and malignant progression of the glioma (8).…”
Section: Introductionmentioning
confidence: 99%